Sentinel node mapping in a pregnant woman with cervical cancer: a case report. Issue 3 (1st April 2006) - Silva, L. B.; Silva-Filho, A. L.; Traiman, P.; Triginelli, S. A.; De Lima, C. F.; Siqueira, C. F.; Lana, A. M.A.; Cunha-Melo, J. R.
Abstract : The possibility of reducing morbidity associated with surgical dissection while maintaining accurate tumor staging is one of the greatest advantages of the sentinel node approach in surgical oncology. The sentinel node mapping has already proven to be useful in melanoma, breast cancer, and vulvar cancer. We report the first case of sentinel node detection by technetium-labeled radiocolloid in a pregnant woman with cervical cancer. The histologic analysis of the operative specimen showed a poorly differentiated squamous carcinoma with metastasis in the sentinel node and a neoplasic embolus in a blood vessel of the placental bed. The lymphatic mapping and sentinel lymph node detection are feasible during pregnancy.